Analisa Kepuasan Pelayanan UMKM Jasa Internet dalam Perspektif Profil Konsumen (Studi Kasus : Konsumen JW Network Indonesia) - M. Dayat; Mochamad Sirodjudin (CV. Satria Jaya, 2023)
This research aim to know: (1) Client profile of JWnet, (2) Customer’s level of fulfillment and (3) Customer’s differential fulfillment of JWnet, assessed by age, sex, occupation, and education level. This applied research using descriptive case of the client of JWnet, using 100 clients as samples. Literature study and questioner used to collect the information. And then data processing uses percentage analysis, One Way ANOVA and Consumer Satisfaction Index analysis. The results of the study show: (1) the profile of the respondents is dominated by men (63%), aged 21-25 years (38%), the majority have university education (66%) and work as students (44%); (2) based on customer satisfaction index is very satisfied (78%), dissatisfied (17%), and satisfied (5%); and (3) and there is a difference in the level of satisfaction, depends on gender, age, and profession, meanwhile there is a significant difference between the level of satisfaction of educated consumers for internet services from JWnet.